A Correlation Study of the Microbiota Between Oral Cavity and Tonsils in Children With Tonsillar Hypertrophy - Xu, He; Tian, Bijun; Shi, Weihua; Tian, Jing; Zhang, Xuexi; Zeng, Jin; Qin, Man (Frontiers in Cellular and Infection Microbiology, 2022)
Tonsillar hypertrophy is a common disease in 3-to-6-year-old children, which may cause serve symptoms like airway obstruction. Microbiological factors play an important role in the etiology of tonsillar hypertrophy. As the starting point of digestive and respiratory tracts, the microbial composition of the oral cavity is not only unique but also closely related to the resident microbiota in other body sites. Here we reported a correlation study of the microbiota between oral cavity and tonsils in children with tonsillar hypertrophy. Saliva, supragingival plaque, and wiped samples from the tonsil surface were collected from both tonsillar hypertrophy patients and participants with healthy tonsils and were then analyzed using Illumina Miseq Sequencing of the 16S rRNA gene. In the tonsillar hypertrophic state, more genera were detected on the tonsil surface than in the tonsil parenchyma, with more intra-microbiota correlations. When tonsillar hypertrophy occurred, both the oral cavity and tonsil surface endured microbiome shift with increased genera category and more active bacterial interactions. Over half of the newly detected genera from the tonsillar hypertrophic state were associated with infection and inflammation process or exhibited antibiotic-resistant characters. Of each individual, the microbial composition and structure of saliva seemed more similar to that of the tonsil surface, compared with the supragingival plaque. In salivary microbiota, genus Johnsonella might be relative with the healthy state of tonsils, while Pseudoxanthomonas might be relative with tonsillar hypertrophy. Our study supported the link between oral microbiota with the healthy and hypertrophic states of tonsils and may provide new directions for future researches in the specific role of oral microbiota in the etiology of tonsil diseases.